Overexpression of Pregnancy Zone Protein in Fat Antagonizes Diet-Induced Obesity Under an Intermittent Fasting Regime - Jiang, Xiaoxiao; Lin, Jun; Dong, Meng; Liu, Xiaomeng; Huang, Yuanyuan; Zhang, Hanlin; Ye, Rongcai; Zhou, Huiqiao; Yan, Chunlong; Yuan, Shouli; Chen, Li; Jiang, Rui; et al. (Frontiers in Physiology, 2022)
The intermittent fasting regimen (IFR) has been certified as an effective strategy for improving metabolism. But the underlying mechanism is still obscure. Beige induction in white adipose tissue (WAT) by IFR may account for this. It has been demonstrated that the erupting of pregnancy zone protein (PZP) from the liver coincides with membrane translocation of grp78 in brown adipocytes during IFR to activate brown adipose tissue (BAT), which may partly explain the metabolic benefits of IFR. Liver-derived PZP appears to be responsible for all metabolic regulatory functions; the effect of boosting energy expenditure disappeared in liver-deficient mice. To verify whether any liver-specific modification was essential for functional PZP, we used the PZP adipose tissue-specific overexpression mice model (PZP TG). We found that the metabolic disorders induced by high-fat diet were improved in PZP TG mice under IFR. Additionally, in addition to the activation of BAT, UCP1 protein and angiogenesis were increased in WAT, as well as the expression of genes associated with glucose utilization. These results demonstrate that PZP fat-specific TG increased the energy conversion of WAT, indicating that WAT may be another direct target for PZP during IFR.